Effect of enterprise resource planning systems and forms of management control on firm’s competitive advantage - Izzeideen A. Alomari,; Amizawati Mohd Amir,; Khairul Azman Aziz,; Sofiah Md Auzair, (Penerbit Universiti Kebangsaan Malaysia, 2018)
In the brick of digitalization industry revolution era, this study signifies the pertinent role of Enterprise Resource Planning Systems (ERPs) towards assisting the organization towards attaining the firm’s mission and goal. This study extends the knowledge by exploring the relationship between ERPs and management control (MC), which in turn enhances firm’s competitive advantage. Realizing the limited empirical work on ERPs from management accounting and control perspective, the discussion would be drawn from business stakeholder’s perspective, instead of from information technology standpoint. The study views ERPs as an important resource in creating the capability to control the business operations and combination of both factors creates the firm’s competitive advantage. Survey questionnaires were administered via email to 972 randomly selected manufacturing firms listed in Federation of Malaysian Manufacturer Directory. Based on the 114 usable responses, the data was analyzed using a structural equation modeling (SEM) approach through partial least square (PLS) software. The findings provide empirical evidence on the significance of ERPs in determining firm’s MC approaches, both technocratic and socio-ideological forms of control. Evidently, these variables do associate positively with competitive advantage. Additionally, the analysis demonstrates that only technocratic form of MC mediates the relationship between ERPs and competitive advantage, but not for socio-ideological control. These findings provide an insight on the relationship among ERPs, form of MC and firm’s competitive advantage, which may be an input for businesses in facing the industrial digitalization era.